2018
DOI: 10.1111/rda.13252
|View full text |Cite
|
Sign up to set email alerts
|

Calcium chloride combined with dimethyl sulphoxide for the chemical sterilization of dogs

Abstract: The aim of this study was to evaluate the effect of intratesticular injection of calcium chloride (CaCl ) combined with dimethyl sulphoxide (DMSO) as a chemical sterilization in dogs. Twelve dogs were divided into two groups: the treated group (n = 6), in which 15 mg/kg of a 7.5% CaCl solution combined with 0.5% DMSO was injected into each testicle (volume range 1.0-4.76 ml); and a control group (n = 6) that received the same volume/kg of 0.9% sodium chloride solution (NaCl). Semen characteristics pre- and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Sterilization of Male Dogs by Intra-testicular Administration of Calcium Chloride Solution fibrosis in the parenchyma which was evident by presence of numerous fibroblasts and fibrocytes. This is in accordance with the findings of Jana and Samanta (2007), Leoci et al (2014), Puri et al (2018) and Silva et al (2018) in dogs. Similar finding was also reported by Jana et al (2005) in male goat, Jana et al (2006) in albino rat, Canpolat et al (2006) in bull, Jana and Samanta (2011) in tom cat and Pereira et al (2018) in bull after chemical castration by calcium chloride.…”
Section: Fc Ncsupporting
confidence: 93%
See 1 more Smart Citation
“…Sterilization of Male Dogs by Intra-testicular Administration of Calcium Chloride Solution fibrosis in the parenchyma which was evident by presence of numerous fibroblasts and fibrocytes. This is in accordance with the findings of Jana and Samanta (2007), Leoci et al (2014), Puri et al (2018) and Silva et al (2018) in dogs. Similar finding was also reported by Jana et al (2005) in male goat, Jana et al (2006) in albino rat, Canpolat et al (2006) in bull, Jana and Samanta (2011) in tom cat and Pereira et al (2018) in bull after chemical castration by calcium chloride.…”
Section: Fc Ncsupporting
confidence: 93%
“…Ahmed (2015) also reported similar results in dogs treated with 20% calcium chloride or clove oil. However, Silva et al (2018) reported no change in serum testosterone level after chemical sterilization of dogs using intra testicular 7.5% calcium chloride (15 mg/kg) combined with dimethyl sulphoxide. Jana et al (2002), Jana and Samanta (2006) and Das and Karmakar (2016) studied chemo-sterilization using intra-…”
Section: Serum Testosterone Assaymentioning
confidence: 98%
“…A single intratesticular injection that could cause the interruption of spermatogenesis would be particularly interesting for its simplicity and speed, as it could be applied to many animals in a single day without the need for specific equipment or environment. In general, zinc gluconate and calcium chloride, the most used substances for chemical castration by intratesticular injection, cause atrophy in the seminiferous tubules, disruption in spermatogenesis, fibrosis and calcification of testicular parenchyma and reduction of testicular volume, together with reduced sperm motility and low sperm count or azoospermia, leading to subfertility or infertility in male animals (Fagundes et al 2014;Vannucchi et al 2015;Silva et al 2018;Leoci et al 2019;Rafatmah, Mogheiseh, and Eshghi 2019). However, many studies report side effects in the treated animals, such as swelling, inflammation, pain, hemorrhage, necrosis and scrotal ulcerations (Levy et al 2008;Oliveira et al 2013;Forz an et al 2014;Rafatmah, Mogheiseh, and Eshghi 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Various chemical sclerotizing agents have been proposed, among them intratesticular injections of calcium chloride or zinc gluconate [63][64][65], intraepididymal injections of chlorhexidine gluconate, zinc arginine, or formalin [28,66,67], and injections of ethanol, silver nitrate, acetic acid, formalin, sodium tetradecyl sulfate, sodium morrhuate, or potassium permanganate into the vas deferens [68]. Among these methods, intratesticular injections of calcium chloride or zinc gluconate have seen limited use in private veterinary practice and particularly in shelter medicine.…”
Section: Sclerotization Methodsmentioning
confidence: 99%